Origines et aspects d’un engagement culturel: l’Italie de Valery Larbaud - Désfalvi-Tóth, András (Verbum – Analecta Neolatina, 2007)
Valery Larbaud had a spiritual inclination to love and admiration which thrilled him and made him find pleasure in the different forms of Beauty, including landscapes and literature, women and works of art. He enjoyed them all, but discovering his own limits made him suffer in spite of the spiritual and physical pleasure he felt. According to Valery Larbaud, Italy appears as "the privileged centre of Romanity" and "the Garden of the Empire", including the Catholic countries of the five continents, Rome being its historical capital. In this paper, we are going to analyse the thematic and technical specificities of the writings about Italy by Valery Larbaud, a citizen of this Empire.